Implications of the Film "Walid" on the Stigma of Sufism in Islam: Penelitian - Sholihin Shobroni; Gregorius Cristison Bertholomeus; RR Roosita Cindrakasih; Dwi Nurahman; Reza Fahlevi Nurpaiz (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is a qualitative study with a descriptive approach, namely an approach that details one by one the main objects in the study which include the Film, the Film "Walid" / "Serial Bidaah", Sufism Teachings. The data used in this study are secondary data that researchers obtained from various credible sources such as books, scientific magazines, and various other sources commonly used in every research. The data obtained were analyzed through the stages of data collection, data reduction, data sampling, and drawing conclusions. The result in this article show First, the presence of the film "Walid"/"Serial Bidaah" can create a negative perception of Sufism, and it is suspected that those who distributed this film have a track record of negative sentiment towards Sufism. This film is suspected of aiming to propaganda so that Sufism is not popular and even ostracized by society. Second, the film can serve as a critique and preventative measure to avoid easily believing individuals who use religious.